Punishment fosters efficiency in the minimum effort coordination game - Fabrice Le Lec; Astrid Matthey; Ondérej Rydval (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Using a laboratory experiment, we examine whether informal monetary sanctions can lead to better coordination in a repeated minimum effort coordination game. While most groups first experience inefficient coordination, the efficiency increases substantially after introducing an ex post sanctioning possibility. Namely, subjects can assign punishment points to other group members upon observing their efforts, which is costly for the punisher but twice as costly for the punished member. By contrast, introducing instead an ex post costless communication possibility fails to permanently increase efficiency. This suggests that decentralized monetary sanctions can play a major role as a coordination device in Pareto-ranked coordination settings, such as teamwork in firms and other organizational contexts.
Keywords: C72; C91; D01; D03; 330; coordination; minimum effort; order-statistic game; punishment; sanction; weakest link; Nichtkooperatives Spiel; Arbeitsleistung; Koordination; Strafe; Test